2013
DOI: 10.5424/sjar/2008064-5293
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic, leaf anatomy, morphology, endophyte presence and ploidy characterization of accessions of Festuca group rubra collected in northern Spain

Abstract: Fifteen accessions of Festuca group rubra collected in northern Spain were characterized and grouped into four Festuca taxa on the basis of leaf anatomy, morphology and ploidy; seven were identified as F. heteromalla; two as F. trichophylla ssp. asperifolia; two as F. nigrescens ssp. microphylla and four as F. rubra ssp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…McMillan (1959) showed that diverse prairie junegrass specimens were infl uenced more by conditions in the local habitat than by their native latitude. (Oliveira et al, 2008). Our data support these later fi ndings in that there were significant fl owering diff erences among accessions within the Table 3.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…McMillan (1959) showed that diverse prairie junegrass specimens were infl uenced more by conditions in the local habitat than by their native latitude. (Oliveira et al, 2008). Our data support these later fi ndings in that there were significant fl owering diff erences among accessions within the Table 3.…”
Section: Discussionsupporting
confidence: 87%
“…(Greene et al, 2008) and fi ne fescue (Festuca spp.) (Oliveira et al, 2008). Cluster analysis revealed a grouping of accessions that had a prostrate growth habit, lower seed yields, smaller seedheads, and shorter plants than the other clusters.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…litoralis (G.F.W. Meyer) Auquier] (Newell and Wood, 2003). In natural stands, prairie junegrass is tolerant of the trampling that occurs on paths and provides complete cover (Dixon, 2000).…”
mentioning
confidence: 99%
“…According to the dry matter yield, meadow fescue (9.1 t ha -1 ) and red fescue (7.0 t ha -1 ) are an important source of fodder in Croatia (Leto et al, 2006), while tall fescue (11.5 t ha -1 ) is in Serbia (Mihajlović et al, 2001). All three fescue species are characterised by a high variability of their agronomic and productive traits (Martincova, 2003;Fang et al, 2004;Oliveira et al, 2008), which provides them with great adaptability to different environmental conditions.…”
mentioning
confidence: 99%